Advanced planning in supply chains : illustrating the concepts using an SAP APO case study - Stadtler, Hartmut (Heidelberg : Springer, 2012)
Advanced Planning Systems (APS) are a key enabler of the supply chain management. However, APS are highly complex and difficult to comprehend. This book provides students with valuable insights into the capabilities of state-of-the-art APS and bridges the gap between theory (model building and solution algorithms), software implementation, and adaptation to a specific business case.
Includes bibliographical references and index.
Keywords: Business logistics -- Planning; Business logistics -- Case studies